Neural Differentiation of Human Umbilical Cord Mesenchymal Stem Cells by Cerebrospinal Fluid - FARIVAR*, Shirin; MOHAMADZADE, Zahra; SHIARI, Reza; FAHIMZAD, Alireza (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: : Farivar S, Mohamadzade Z, Shiari R, Fahimzad AR. Neural Differentiation of Human Umbilical Cord Mesenchymal Stem Cells by Cerebrospinal Fluid. . Iran J Child Neurol. 2015 Winter; 9(1):87-93. Abstract Objective Wharton’s jelly (WJ) is the gelatinous connective tissue from the umbilical cord. It is composed of mesenchymal stem cells, collagen fibers, and proteoglycans. The stem cells in WJ have properties that are interesting for research. For example, they are simple to harvest by noninvasive methods, provide large numbers of cells without risk to the donor, the stem cell population may be expanded in vitro, cryogenically stored, thawed, genetically manipulated, and differentiated in vitro. In our study, we investigated the effect of human cerebrospinal fluid (CSF) on neural differentiation of human WJ stem cells. Material & Methods The cells in passage 2 were induced into neural differentiation with different concentrations of human cerebrospinal fluid. Differentiation along with neural lineage was documented by expression of three neural markers: Nestin, Microtubule-Associated Protein 2 (MAP2), and Glial Fibrillary Astrocytic Protein (GFAP) for 21 days. The expression of the identified genes was confirmed by Reverse Transcriptase PCR (RT-PCR). Results Treatment with 100 and 200μg/ml CSF resulted in the expression of GFAP and glial cells marker on days 14 and 21. The expression of neural-specific genes following CSF treatment was dose-dependent and time-dependent. Treatment of the cells with a twofold concentration of CSF, led to the expression of MAP2 on day 14 of induction. No expression of GFAP was detected before day 14 or MAP2 before day 21, which shows the importance of the treatment period. In the present study, expression analysis for the known neural markers: Nestin, GFAP, and MAP2 using RT-PCR were performed. The data demonstrated that CSF could play a role as a strong inducer. Conclusion RT-PCR showed that cerebrospinal fluid promotes the expression of Nestin, MAP2, and GFAP mRNA in a dose-dependent manner, especially at a concentration of 200 μl/ml. In summary, CSF induces neurogenesis of WJ stem cells that encourages tissue engineering applications with these cells for treatments of neurodegenerative defects and traumatic brain injury. References Gage, F. H. Mammalian neural stem cells. Science 2000 Feb 25;287(5457):1433-8. Da Silva Meirelles L, Chagastelles PC, Nardi NB. Mesenchymal stem cells reside in virtually all postnatal organs and tissues. J Cell Sci 2006 Jun 1;119(Pt 11):2204- 13. Epub 2006 May 9. Pittenger MF, Mackay AM, Beck SC, Jaiswal RK, Douglas R, Mosca JD, Moorman MA, Simonetti DW, Craig S, Marshak DR. Multilineage potential of adult human mesenchymal stem cells Science 1999 Apr 2;284(5411):143-7. Tse WT, Pendleton JD, Beyer WM, Egalka MC, Guinan EC. Suppression of allogeneic T-cell proliferation by human marrow stromal cells: implications in transplantation. Transplantation 2003 Feb 15;75(3):389- 97. Le Blanc K. Immuno-modulatory effects of fetal and adult mesenchymal stem cells. Cytotherapy 2003;5(6):485-9. Stenderup K, Justesen J, Clausen C, Kassem M. Aging is associated with decreased maximal life span and accelerated senescence of bone marrow stromal cells. Bone 2003 Dec;33(6):919-26. Bongso A, Fong CY, Gauthaman K. Taking stem cells to the clinic: major challenges. J Cell Biochem 2008 Dec 15;105(6):1352-60. doi: 10.1002/jcb.21957. Fong CY, Chak LL, Biswas A. Human Wharton’s jelly stem cells have unique transcriptome profiles compared to human embryonic stem cells and other mesenchymal stem cells. Stem Cell Rev 2011 Mar;7(1):1-16. doi: 10.1007/s12015-010-9166-x. Troyer DL, Weiss ML. Wharton’s jelly-derived cells are a primitive stromal cell population. Stem Cells 2008 Mar; 26(3):591-9. Epub 2007 Dec 6. Yuan X, Desiderio DM. Proteomics analysis of human cerebrospinal fluid. J Chromatogr B Analyt Technol Biomed Life Sci 2005 Feb 5;815(1-2):179-89. Thompson, EJ. Cerebrospinal fluid. J Neurol Neurosurg Psychiatry 1995 Oct;59(4):349-57. Alcazar A, Regidor I, Masjuan J, Salinas M, Alvarez- Cermeno JC. Induction of apoptosis by cerebrospinal fluid from patients with primary-progressive multiple sclerosis in cultured neurons. Neurosci Lett 1998 Oct 16;255(2):75-8. Colombo JA, Napp MI. Cerebrospinal fluid from L-dopa-treated Parkinson’s disease patients is dystrophic for various neural cell types exvivo: effects of astroglia. Exp Neurol 1998 Dec;154(2):452-63. Redzic ZB, Preston JE, Duncan JA, Chodobski A, Szmydynger-Chodobska J. The choroid plexus-cerebrospinal fluid system: from development to aging. Current topics in developmental biology 2005; (71): 1-52. Bachy I, Kozyraki R, Wassef M. The particles of the embryonic cerebrospinal fluid: how could they influence brain development? Brain Res Bull 2008 Mar 18;75(2- 4):289-94. doi: 10.1016/j.brainresbull.2007.10.010. Parada C, Gato A, Bueno D. Mammalian embryonic cerebrospinal fluid proteome has greater apo-lipoprotein and enzyme pattern complexity than the avian proteome. Journal of proteome research 2005; 4(6): 2420- 2428. Martin C, Bueno D, Alonso MI, Moro JA, Callejo S, Parada C, Martin P, Carnicero E, Gato A. FGF2 plays a key role in embryonic cerebrospinal fluid trophic properties over chick embryo neuro epithelial stem cells. Dev Biol 2006 Sep 15;297(2):402-16. Epub 2006 May 19. Huttner HB, Janich P, Kohrmann M, Jaszai J, Siebzehnrubl F, Blumcke I, Suttorp M, Gahr M, Kuhnt D, Nimsky C. The stem cell markerprominin-1/CD133 on membrane particles in human cerebrospinal fluid offers novel approaches for studying central nervous system disease. Stem Cells 2008 Mar;26(3):698-705. Nordin C, Gupta RC, Sjodin I. Cerebrospinal fluid amino acids in pathological gamblers and healthy controls. Neuropsychobiology 2007;56(2-3):152-8. doi: 10.1159/000115782. Epub 2008 Feb 7. Gato A, Martin P, Alonso MI, Martin C, Pulgar MA, Moro JA. Analysis of cerebro-spinal fluid protein composition in early developmental stages in chick embryos. J Exp Zool A Comp Exp Biol 2004 Apr 1;301(4):280-9. Mitchell KE, Weiss ML. Matrix cells from Wharton’s jelly form neurons and glia. Stem Cells 2003;21(1):50-60. Marcus AJ, Woodbury D. Fetal stem cells from extra-embryonic tissues: do not discard. J Cell Mol Med 2008 Jun;12(3):730-42. doi: 10.1111/j.1582- 4934.2008.00221.x. Epub 2008 Jan 11. Miao Z, Jin J, Chen L, Zhu J, Huang W, Zhao J, Quian H, Zhang X. Isolation of mesenchymal stem cells from human placenta: comparison with human bone marrow mesenchymal stem cells. Cell Biol Int 2006 Sep;30(9):681-7. Epub 2006 Apr 22. In ‘tAnker PS, Scherjon SA, Kleijburg-van der Keur C, Noort WA, Claas FHJ, Willemze R, Fibbe WE, Kanhai HHH. Amniotic fluid as a novel source of mesenchymal stem cells for therapeutic transplantation. Blood 2003;102(4):1548-49. Magatti M, De Munari S, Vertua E, Gibelli L, Wengler GS, Parolini O. Human amnion mesenchyme harbors cells with allogeneic T-cell suppression and stimulation capabilities. Stem Cells 2008 Jan;26(1):182-92. Epub 2007 Sep 27. Kang XQ, Zang WJ, Bao LJ, Li DL, Xu XL, Yu XJ. Differentiating characterization of human umbilical cord blood-derived mesenchymal stem cells in vitro. Cell Biol Int 2006 Jul;30(7):569-75. Epub 2006 Mar 6. Kern S, Eichler H, Stoeve J, Kluter H, Bieback K. Comparative analysis of mesenchymal stem cells from bone marrow, umbilical cord blood, or adipose tissue. Stem Cells 2006 May;24(5):1294-301. Epub 2006 Jan 12. Wagner W, Wein F, Seckinger A, Frankhauser M, Wirkner U, Krause U, et al. Comparative characteristics of mesenchymal stem cells from human bone marrow, adipose tissue, and umbilical cord blood. Exp Hematol 2005 Nov;33(11):1402-16. Jackson JS, Golding JP, Chapon C, Jones WA, Bhakoo KK: Homing of stem cells to sites of inflammatory brain injury after intracerebral and intravenous administration: a longitudinal imaging study. Stem Cell Res Ther 2010 Jun 15;1(2):17. doi: 10.1186/scrt17. Romanov YA, Svintsitskaya VA, Smirnov VN. Searching for alternative sources of postnatal human mesenchymal stem cells: candidate MSC-like cells from umbilical cord. Stem Cells 2003;21(1):105-10. Weiss ML, Medicetty S, Bledsoe AR. Human umbilical cord matrix stem cells: Preliminary characterization and effect of transplantation in a rodent model of Parkinson’s disease. Stem Cells 2006 Mar;24(3):781-92. Carlin R, Davis D, Weiss M. Expression of early transcription factors Oct4, Sox2 and Nanog by porcine umbilical cord (PUC) matrix cells. Reprod Biol Endocrinol. 2006 Feb;6(4):8. Usha Nekanti, Sumitava Dastidar, Parvathy Venugopal, Satish Totey and Malancha Ta. Increased Proliferation and Analysis of Differential Gene Expression in Human Wharton’s Jelly-derived Mesenchymal Stromal Cells under Hypoxia. Int J Biol Sci. 2010; 6(5): 499–512.